2020
DOI: 10.3390/su12219204
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Process Toward Corporate Sustainability at a Thai SME

Abstract: Given that corporate leaders seek to ensure the long-term sustainability of their organization, this study explores how a business adopting a Thai Sufficiency Economy philosophy improves its sustainability performance. Adopting the Sufficiency Thinking model as the research framework, this study uses a qualitative research approach with a set of different data collection techniques to explore a sample Small–Medium-sized Enterprise (SME) called Plan Creation. Collected data are identified as themes, according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have concluded with the substantial impact of leadership spurring innovation [30][31][32][33]. Sustainable leadership has been recommended as highly effective leadership to deal with environmental challenges [34]. Strong sharing vision, support for ideas generation, knowledge sharing, long-lasting relationships, ethically and socially responsible behaviors are core attributes of sustainable leaders [28,35].…”
Section: Sustainable Leadership and Environmental Innovationmentioning
confidence: 99%
“…Previous studies have concluded with the substantial impact of leadership spurring innovation [30][31][32][33]. Sustainable leadership has been recommended as highly effective leadership to deal with environmental challenges [34]. Strong sharing vision, support for ideas generation, knowledge sharing, long-lasting relationships, ethically and socially responsible behaviors are core attributes of sustainable leaders [28,35].…”
Section: Sustainable Leadership and Environmental Innovationmentioning
confidence: 99%
“…An important aspect of leadership competence that is highly relevant in the Industry 4.0 era is the ability to manage people from different cultures. This aspect of leadership competence is called "cultural intelligence" [58]. The concept of Emotional Quotient (EQ) intelligence fits perfectly into this stream of leadership in Industry 4.0.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Valeri (2021), for instance, made the case that an organization's response to environmental factors affects the operational styles it chooses. Kantabutra and Punnakitikashem (2020) stress that the organizational design of a business should be modified to consider both internal elements, such as workplace settings, and external circumstances. The word "contingency" emphasizes the idea that one item depends on another or that one quality is impacted by another (Kriemadis et al, 2021).…”
Section: Theoretical Review Conceptual Clarification and Hypothesis D...mentioning
confidence: 99%